Fragmented fibre (including microplastic) pollution from textiles. Issue 3 (3rd July 2021) - Palacios-Marín, Alma V.; Tausif, Muhammad
Abstract: The threat of microplastic (MP) pollution to our ecosystem is well established. The presence of natural, regenerated, and synthetic fragmented fibres (FF) and their abundance in terrestrial and aquatic environments has been extensively reported. All textiles release FF during their lifecycle, not limited to plastics, which find their way to the environment through different dispersal pathways. Beyond the nature of the polymer, the FF can also can be a carrier of hazardous chemicals. The ubiquitous nature of MPs (and FF) has widely placed them as one of the most enduring and pervasive anthropogenic pollutants. This review is focused on FFs generated and released from textiles during wet (predominantly laundering) and dry exposure conditions. A summary and critical analysis of the current methods to generate, collect, measure, and characterise FF from textile laundry effluent is presented. The impact of key parameters on the release of FF is summarised; including washing equipment/conditions, filtration procedures, characterisation techniques, and the effect of textile materials and structure. The results from key publications are tabulated for direct comparisons, this includes estimated number of FF released per washing cycle and length distribution profile. Though the wet route of release has gained more attention, the release through dry routes is also significant. Hence, a detailed overview of the collection and characterisation of FF from dry routes (atmospheric deposition and textile abrasion) was important. Finally, a comprehensive overview of latest research and industrially-applied mitigation strategies to limit the release of FF from textile sources during laundry is included. The impact of MPs (and FF) is briefly outlined covering the environment, human health and degradation. Improved plastics with reduced environmental impact, plastic recycling and reduced consumption are vital. Still, the release of FFs from textiles remains a challenge since their production is unintentional.